2022
DOI: 10.1111/fcp.12827
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nerve regeneration with nimodipine treatment after sciatic nerve injury

Abstract: Peripheral nerve injuries (PNI/s) are common orthopedic conditions, characterized by motor and sensory deficits in the damaged region. There is growing evidence that the L‐type calcium channel antagonist nimodipine has neuroprotective and neuroregenerative effects in animal models of neurological disorders. The efficacy of nimodipine on improving motor function and sensation following a sciatic nerve crush model was investigated in male Wistar rats as a model of PNI. At different time periods following damage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The stroma consists of three layers of connective tissues, while the parenchyma is formed by the nerve fibers, namely, axons and Schwann cells. The nerve fibers can be myelinated if the Schwann cells cover a single axon, or a single Schwann cell can interact with a group of axons resulting unmyelinated nerve fibers [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The stroma consists of three layers of connective tissues, while the parenchyma is formed by the nerve fibers, namely, axons and Schwann cells. The nerve fibers can be myelinated if the Schwann cells cover a single axon, or a single Schwann cell can interact with a group of axons resulting unmyelinated nerve fibers [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental trial, 30 female Wistar rats, weighing between 180 and 200 grams, were purchased from the Pasteur Institute and transferred to the Laboratory Center of Azad Islamic University, Tehran Branch. To allow the rats to adapt to the environment and to control confounding factors, the rats were acclimated for two weeks before the start of the protocols (24,25). The laboratory environment was prepared according to the following standards: Regulation of relative humidity at 50% ± 10%, regulation of light-dark cycles to 12/12 hours, temperature maintained at 25 ± 2 degrees Celsius, a ventilation system with a silent fan, housing 6 rats in a standard cage, and providing free access to tap water and rat chow.…”
Section: Animalsmentioning
confidence: 99%
“…In the last decade, the regeneration potential of a number of molecular and gene agents has been evaluated in the mouse sciatic nerve injury model. They have shown potential applications in preclinical studies ( Al-Saedi et al, 2023 ; Elhessy et al, 2023 ; Ferdowsi et al, 2023 ).…”
Section: Preclinical Studies Modeling Peripheral Neuropathies or Peri...mentioning
confidence: 99%
“…The findings showed that motor and sensory neuron functions increased after treatment. Nimodipine can both reduce apoptosis and promote axon regeneration likely by modulating the CREB signaling pathway and suppressing pro-inflammatory factors ( Al-Saedi et al, 2023 ).…”
Section: Preclinical Studies Modeling Peripheral Neuropathies or Peri...mentioning
confidence: 99%